Development Of Interactive E-Modules Based On Animated Videos To Improve Critical Thinking Skills In History Learning Media Courses - Sidiq, Ric; Najuah, N; Syarifah, Syarifah; Saragih, Anggi (International Journal of Educational Research & Social Sciences, 2023)
This research aims to produce interactive E-Module products based on animated videos to improve critical thinking skills in history learning media courses. The target of this research is products developed /valid for use according to experts and users. The method used is the research and development method or Research &; Development (R&D). To produce the product, testing its feasibility and effectiveness is carried out in accordance with the development goals. The research was carried out in the Department of History Education with the observed modifiers, namely history education students class of 2020 as the target targets and products developed. Data collection techniques are carried out through observation, and questionnaires. With data analysis techniques with qualitative descriptive and quantitative descriptive. From the results of the research conducted, data were obtained: 1). The results of material expert validation received a value of 75 with a percentage of 93.75% in the "Very Valid" category (No Revision Needed). 2). Media Expert Validation Results get a score of 74 with a percentage of 92% in the "Very Valid" category (No Revision Required). 3). The results of the small group trial obtained a percentage score of 79.62% with an unrevised assessment. Then the results of the group trial were obtained a percentage score of 83.79% with an unrevised assessment. As well as the results of large group trials obtained a score of 85.46% with unrevised assessments. With these results, the media is declared very feasible to use.